Hubungan Motivasi Kerja Dan Status Gizi Dengan Produktivitas Kerja Perawat Di Bangsal Rawat Inap Pada Masa Pandemi Covid-19 Di Rsud Kabupaten Kepahiang - Aprianti, Rina; Suryani; Dirhan; Novi Ade Suryani; Riani Safitri (Gayaku Publisher, 2024)
The tight competition for human resources (HR), especially nurses, is felt by hospitals. Every job requires human resources (HR) to improve the quality of their work. The importance of work productivity for nurses is an evaluation material to make continuous improvements for all components of the hospital, improving the quality of work results by the hospital. This type of research uses an Analytical Survey approach with a Cross Sectional design. The sample in this study were all inpatient nurses at the Kepahiang Regency Hospital. Data collection in this study used primary data by distributing questionnaires. Technical data analysis was carried out by Chi Square test analysis through the SPSS program. To determine the closeness of the relationship using the Contigency Coefficient (C) statistical test. The results showed that out of 76 respondents there were 32 (42.1%) respondents with poor work motivation, there were 46 (60.5%) respondents with abnormal nutritional status, there were 32 (42.1%) respondents whose work productivity was not good at the Kepahiang Regency Hospital. There is a significant relationship between work motivation and work productivity of nurses in inpatient wards during the covid-19 pandemic at the Kepahiang Regency Hospital with a p value (0.009); C: 0.286. The results of this study are expected to be a reference in improving the work productivity of nurses in inpatient wards during the covid-19 pandemic at the Kepahiang Regency Hospital by conducting internal training, brainstorming activities, holding outstanding nurses, making and filling out nursing activity report forms.